2021
DOI: 10.1055/a-1509-3676
|View full text |Cite
|
Sign up to set email alerts
|

Delta Neutrophil Index as a Promising Biomarker for Placental Implantation Disorders

Abstract: Objective We aimed to investigate the value of maternal serum delta neutrophil index (DNI) levels in predicting placenta accreta spectrum in patients with placenta previa. Methods The patients who were found to have placenta previa totalis were included in our study. Location of placental implantation and depth of myometrial invasion were defined by transabdominal and transvaginal 2D gray scale and Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
2
8
2
Order By: Relevance
“…Tasgoz et al indicated that there was an increase in NLR and PLR in PP cases but did not find significant differences in PDW and RDW values 21 . In a recent study conducted by Karakoc et al, there was no difference in NLR and PLR values, but delta neutrophil index was significantly higher between PP and PAS cases 16 . In our study, PDW and RDW were lower and MPV, NLR, PLR were higher in PAS cases compared to PP cases.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Tasgoz et al indicated that there was an increase in NLR and PLR in PP cases but did not find significant differences in PDW and RDW values 21 . In a recent study conducted by Karakoc et al, there was no difference in NLR and PLR values, but delta neutrophil index was significantly higher between PP and PAS cases 16 . In our study, PDW and RDW were lower and MPV, NLR, PLR were higher in PAS cases compared to PP cases.…”
Section: Discussioncontrasting
confidence: 68%
“…21 In a recent study conducted by Karakoc et al, there was no difference in NLR and PLR values, but delta neutrophil index was significantly higher between PP and PAS cases. 16 In our study, PDW and RDW were lower and MPV, NLR, PLR were higher in PAS cases compared to PP cases.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…However, more studies should be conducted to determine whether there is a predictive marker for placental invasion anomalies. 45 Our results suggest that the DNI measurement at ICP may be a valuable marker; however, large-scale studies should be performed to verify this result.…”
Section: Discussionmentioning
confidence: 67%